2004
DOI: 10.1007/s00432-003-0517-8
|View full text |Cite
|
Sign up to set email alerts
|

PTEN immunohistochemical expression is suppressed in G1 endometrioid adenocarcinoma of the uterine corpus

Abstract: PTEN protein expression was decreased in well-differentiated and less growth-aggressive endometrial carcinoma with wild-type p53 gene and high levels of ER and PR. This suggests that disturbed PTEN expression occurs in an early phase of the tumorigenesis of well-differentiated endometrial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 29 publications
6
27
0
1
Order By: Relevance
“…A finding that agrees with Kapucuoglu et al (2007); Abd El-Maqsoud and ElGelany (2009); Sarmadi et al (2009);and Lee et al (2012), whose studies reported a significantly lower PTEN scores in atypical hyperplasia compared with endometrial hyperplasia, and incompatible with Kimura et al (2004) and Xiong et al (2010), who showed no significant differences among subtypes of hyperplasia. (72) EECA versus PE and EH (P < 0.001) for both; AH versus PE and EH (P = 0.0015, P < 0.001); EECA versus AH (P = 0.2) nonsignificant, respectively.…”
Section: Discussionsupporting
confidence: 67%
“…A finding that agrees with Kapucuoglu et al (2007); Abd El-Maqsoud and ElGelany (2009); Sarmadi et al (2009);and Lee et al (2012), whose studies reported a significantly lower PTEN scores in atypical hyperplasia compared with endometrial hyperplasia, and incompatible with Kimura et al (2004) and Xiong et al (2010), who showed no significant differences among subtypes of hyperplasia. (72) EECA versus PE and EH (P < 0.001) for both; AH versus PE and EH (P = 0.0015, P < 0.001); EECA versus AH (P = 0.2) nonsignificant, respectively.…”
Section: Discussionsupporting
confidence: 67%
“…In summary, our data strongly suggest that supraphysiologic activation of ERa is, in vivo, an obligatory pathway for the development of endometrial lesions consequent to loss of Pten and activation of Akt. The functional connection between these molecules is further underlined by the fact that loss of PTEN is typically found in EECs expressing high levels of ERa (21). Similarly, the same axis is likely to play a pivotal role in the development of ERa-positive breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK activation by metformin is not only necessary for inhibition of gluconeogenesis in hepatocytes and reduction of Acetyl-CoA carboxylase (ACC) activity and hence fatty acid oxidation [75], but also for its growth-inhibitory effect in epithelial cells [76] an effect associated with decreased mTOR and S6 kinase activation. Several studies have now demonstrated that activation of AMPK suppresses mTOR signaling induced by growth factors and amino acids [40,[78][79][80][81] directly or indirectly (via TSC2). Signaling through mTOR up-regulates many energy-consuming cellular processes: mTOR has a central role in regulating cell growth by controlling mRNA translation, ribosome biogenesis, autophagy, and metabolism (reviewed in Refs.…”
Section: Targeting Ampk By Metforminmentioning
confidence: 99%